ILMIZI: Innovation Learning Model for Natural Science and Environmental Learning based on HOTS - Ichsan, Ilmi Zajuli (International Journal for Educational and Vocational Studies, 2019)
Natural science and environmental learning in the 21st century require Higher order thinking skills (HOTS). The purpose of this study was to develop an ILMIZI learning model. The method used is research and development carried out in June-July 2019. The results of the study showed that the ILMIZI model syntax consists of 6 stages, start from Identify problem, Limitation problem, Make mind map, Interpret result, Analyze result, Interaction and evaluate. The six stages are the results of development which are expected to have an impact on the rise of HOTS. Validation results from various learning experts and teachers showed a score of 3.74 with a percentage of  93.50%  and a very valid category which means that the ILMIZI model is suitable for use in natural science learning (biology, physics, chemistry) and environmental learning at all levels of education. The conclusion is that the ILMIZI learning model was suitable for learning and expected to have an impact on HOTS students